Pelaksanaan Layanan Informasi dengan Teknik Diskusi untuk Meningkatkan Perencanaan Karir Pada Siswa Di SMA Negeri 1 Percut Sei Tuan - Nasution, Yeni Rahman; Manurung, Purbatua; Sinaga, Harwansyah Putra (Education Achievement: Journal of Science and Research, 2024)
This research aims to improve students' career planning at SMA Negeri 1 Percut Sei Tuan through the implementation of information services using discussion techniques. The main focus is to identify and improve students' understanding of career choices that suit their interests and abilities, as well as to increase their involvement in career planning through interactive discussions. The method used in this research is Counseling Guidance Action Research (PTBK), which is a strategy for improving educational services in the classroom context. This research was carried out in two cycles, each involving observation, interviews and questionnaires to collect qualitative and quantitative data. Data was collected through documentation, observation and questionnaire techniques which were processed with quantitative analysis using a modified Likert scale. Evaluation is carried out based on increasing the percentage of students with high career planning. In Cycle I, the results of the questionnaire showed that 60% of students experienced an improvement in their career planning after the information service. However, these results have not reached the success target of 75%. Observations revealed that student involvement in discussions varied, with some students active and others less involved. In Cycle II, after improvements in implementation methods, 80% of students showed improvement in their career planning, achieving the set targets. These results indicate that information services with discussion techniques significantly improve students' understanding of career planning and their ability to plan their future better.